2007
DOI: 10.1002/jmv.20934
|View full text |Cite
|
Sign up to set email alerts
|

Variations in the core promoter/pre‐core region in HBV genotype C in Japanese and Northern Vietnamese patients

Abstract: Hepatitis B virus (HBV) subgenotypes Cs (C1)and Ce (C2) are common in East Asia. To investigate the genomic difference of HBV genotype C between two separated regions, 50 subgenotype Cs-infected Vietnamese and 70 subgenotype Ce-infected Japanese patients were enrolled for analysis. The patients were categorized to either a hepatocellular carcinoma group (HCC) or a non-HCC group including liver cirrhosis, chronic hepatitis, and asymptomatic carriers. HBV serology, HBV-DNA level, and variations in core promoter/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…In the case of subgenotypes from genotype C, similar observations have been published recently. While a direct association of subgenotypes C1/C2 with the prevalence of hepatocellular carcinoma (HCC) is under debate [Tseng et al, 2007;Chan et al, 2008], there are clear differences in patients with HCC infected with either C1 or C2 Truong et al, 2007;Wang et al, 2007a,b;Yuan et al, 2007;Sung et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of subgenotypes from genotype C, similar observations have been published recently. While a direct association of subgenotypes C1/C2 with the prevalence of hepatocellular carcinoma (HCC) is under debate [Tseng et al, 2007;Chan et al, 2008], there are clear differences in patients with HCC infected with either C1 or C2 Truong et al, 2007;Wang et al, 2007a,b;Yuan et al, 2007;Sung et al, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, among HBV carriers, the A1762T/G1764A mutation is more frequently found in genotype C than genotype B [19,31] . However, an independent study on a comparison of HBV genotype C from Vietnam and Japan showed mutations at different positions in the core promoter/precore region of HBV [32] , indicating that the effect of mutation on liver carcinogenesis may not be universal. In addition, some mutations in HBx protein, in particular for HBV genotype C, have been shown to be significantly associated with HCC.…”
Section: Introductionmentioning
confidence: 99%
“…Each subgenotype has a unique geographic distribution and virological characteristics. Vietnam is one of the most endemic areas of HBV infection, and the prevalence of HBV subgenotypes in patients with chronic hepatitis in Vietnam has been reported [5][6][7][8] . HBV subgenotypes C1 and B4 are frequently found in Vietnam.…”
mentioning
confidence: 99%